Finance Unleashed Leveraging the CFO for Innovation - Lind, Magnus (Springer International Publishing, 2018)
Fast moving, to the point, and rooted in first-hand executive experiences, this book is for people of vision and action, and for creating the conditions required for growth, innovation, and increased competitive advantage. Finance Unleashed is based on a series of interactive interviews with a diverse group of global influencers and executives, all of which will challenge readers to think laterally and find inspiration in the new role of finance. Cases and interviewees represent organizations such as UPS and DHL, and the London School of Economics, and approaches such as Lean Six Sigma, innovation, customer-centricity, the financial supply chain, and behavioral procurement. The authors' goal is to serve as a catalyst for leaders who are positioned to make meaningful changes today. The book includes a practical model to help executive teams redesign and refocus finance to drive business leadership - with an emphasis on the CFO. The model has three primary components: 1) Customer-Centricity - Listen and Map; 2) Process - Structure and Technology; and 3) Innovation - Create and Measure. These are presented as phases that each executive team will need to consider based on the goals and maturity level of their organization. For the CFO and ambitious finance executives, Finance Unleashed presents a path forward towards success and career advancement. For the CEO and the board, it presents an expanded vision for what financial organizations are capable of. .